DRAMA, MANUVER DAN CAWE-CAWE POLITIK MENJELANG PILPRES 2024 - Hamdi, Saipul; Ikmal Maulana; Ihfan Rahmawadi; Fatimatuzzahro (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The 2024 presidential election (Pilpres) contains distinct characteristics that differ from past presidential elections. The 2024 presidential election contest is very complex and unique due to the changing composition of the coalition of political parties supporting the presidential and vice presidential candidates, including President Jokowi's shifting support, which is no longer aligned with his party, the Indonesian Democratic Party of Struggle (PDIP). This article will look at the political events that unfolded during the 2014 presidential election, such as Anies Baswedan's refusal to run as a presidential candidate, Jokowi's feud with the PDIP, and neutrality or interference during the election. This research employs qualitative approaches using data collection procedures through the desch study, incorporating media. The findings revealed that Jokowi intervened politically by backing the 02 group in order to assure the continuance of the previously implemented development strategy. There are hints of substantial participation by Jokowi in the process of deciding presidential candidates by supporting parties, such as the nomination of Anies Baswedan. Other data indicate that Jokowi and his family's political moves in the 2024 presidential race contradict the PDIP, culminating in open conflict between the PDIP elite and Jokowi. The appointment of Gibran as Prabowo's vice presidential candidate following the Constitutional Court's decision has sparked debate in the community and led to charges of Jokowi's lack of impartiality in this presidential race. Meanwhile, international media outlets such as Al Jazeera covered the presidential election and reported that Gibran met public expectations.